Pengaruh Profitabilitas, Struktur Good Corporate Governance dan Kualitas Audit terhadap Audit Delay - Purba, Darwin Marasi (Jurnal Ilmiah Akuntansi Kesatuan, 2018)
This study is aimed at collecting empirical evidence about the influence of profitability, and good corporate governance w h i c h consisted of the board size, the independent commisioners, audit committee size and audit quality on the audit delay.The populations of this research are manufacturing companies of consumer goods industry sector listed in Indonesia Stock Exchange in the year of 2015-2016 which includes 56 companies, using purposive sampling technique. Methods of data analysis used in this research are descriptive statistical analysis and multiple linear regressions.The results indicate that profitability, good corporate governance and audit quality have a simultaneously significant effect on the audit delay. However, partial test results show that the profitability and the size of audit committee are not affecting on the audit delay. Meanwhile, the board size, independent commissioners and audit quality have a significant effect on the audit delay